Penerapan Asas Nebis in Idem yang Diajukan di Peradilan Berbeda Berdasarkan Asas Contante Justitie: (Studi Putusan Nomor 287/Pdt.G/2023/PA.Skh) - Setiawan, Andi; Junaidi, Amir; Khaerudin, Ariy; Yudanto, Dika (Universitas Serang Raya, 2023)
This research aims to analyze the application of the principle of nebis in idem in the handling of civil case Number 287/Pdt.G/2023/PA.Skh. which corresponds to the principle of contante Justitie and to know and analyze the handling of cases carried out by judges who examine, hear, and decide cases handled by the Sukoharjo Religious Court, by looking at the considerations of judges in applying the principle of nebis in idem. This research is normative legal research, using secondary data which is processed using qualitative techniques. The results of this study indicate that: (1) the handling of civil case Number 287/Pdt.G/2023/PA.Skh. in its decision is appropriate and has applied the principle of nebis in idem properly, because the elements of nebis in idem as required in the Civil Code have cumulatively been fulfilled; (2) the considerations given by the panel of judges in giving the decision are appropriate and correct based on applicable legal principles. (3) cases containing elements of nebis in idem must be filed an exception and an exception can only be filed in the first answer along with a rebuttal to the subject matter. It is recommended that in the future a dismissal process can be carried out before cases related to nebis in idem are examined and tried like the mechanism in the state administrative court, in order to provide legal certainty for justice seekers as well as implement the principles of fast, simple, and light costs.